Efficacy of psychological interventions for young adults with mild-to-moderate depressive symptoms: A meta-analysis. (August 2022) - Medina, J.C.; Paz, C.; García-Mieres, H.; Niño-Robles, N.; Herrera, J.E.; Feixas, G.; Montesano, A.
Abstract: Background: Psychological interventions are commonly used to treat mild-to-moderate depression, but their efficacy in young adults has not been exhaustively addressed. This meta-analysis aims to establish it in comparison to no treatment, wait-list, usual treatment, passive interventions, and other bona-fide treatments. Methods: The search was conducted in Scopus, MEDLINE, PsycINFO, ClinicalTrials.gov, the ISRCTN Registry, Cochrane CENTRAL, Clarivate BIOSIS Previews and the METAPSY database, retrieving studies from the start of records to April 2020. Eligibility criteria included samples of 16–30 years experiencing mild-to-moderate depressive symptoms and participating in randomized controlled trials (RCTs), non-RCTs, or pre-post studies measuring depressive symptomatology and featuring psychological treatments. Results: Up to 45 studies met criteria, consisting of 3, 947 participants, assessed using the Quality Assessment Tool for Quantitative Studies and their results meta-analyzed assuming random effects. Psychological interventions proved to be efficacious in RCTs compared to no treatment ( g  = −0.68; 95% CI  = −0.87, −0.48) and wait-list ( g  = −1.04; 95% CI  = −1.25, −0.82), while depressive symptoms also improved in pre-post studies ( g  = −0.99; 95% CI  = −1.32, −0.66). However, intervention efficacy was similar to usual care, passive, and bona-fide comparators. The heterogeneity found, a likely reporting bias and the low quality of most studies must be considered when interpreting these results. Conclusions: Psychological treatments are efficacious to reduce depressive symptoms in young adults, but comparable to other interventions in the mild-to-moderate range. Moderators like depression severity or therapist involvement significantly influenced their efficacy, with results encouraging clinicians to adopt flexible and personalized approaches. Highlights: Psychotherapy is efficacious to treat mild-to-moderate depressive symptoms in young adults. Therapists are encouraged to personalize treatments and adopt flexible approaches. Baseline severity and therapist involvement emerge as relevant efficacy moderators.